Hydroacoustic Assessment of Zooplankton Abundance in Southeastern Pari Island Waters, Jakarta Bay - Muhammad Ravelino; Henry Munandar Manik; Adriani Sunuddin; La Elson (Jurnal Kelautan Tropis, 2026)
Hydroacoustic techniques provide a swift, non-intrusive approach to quantifying pelagic organisms; however, their application for zooplankton evaluations within Indonesian coastal waters remains underexplored. This investigation assesses the efficacy of a 200 kHz single-beam echosounder (SIMRAD EK15) for estimating zooplankton density and vertical distribution in the coastal marine environment surrounding Southeast Pari Island, Jakarta Bay. Acoustic information was amassed during a two-day survey conducted in June 2025 across 14 designated stations ranging from nearshore to offshore, augmented by vertical plankton-net collections and in situ measurements of temperature, salinity, density, and sound velocity. Volume backscattering strength (SV) was analyzed utilizing Echoview 4.0 and compared against laboratory-derived zooplankton density. Zooplankton density varied from 208.33 to 828.61 ind/L, with generally elevated figures observed at offshore stations, implying increased biological productivity. A total of 9,934 individuals representing 45 genera and 9 orders were identified, predominantly comprising copepods (including nauplii and Calanoida), yielding a Shannon-Wiener index of 2.40, a Simpson index of 0.80, and an evenness index of 0.63, indicative of a diverse and relatively equilibrated community. Acoustic findings illustrated distinct scattering layers and heightened SV values primarily within the upper 0-30 m of the water column, suggesting pronounced vertical structuring of zooplankton in relation to water column stratification. The correlation between mean SV and zooplankton density was found to be positive yet weak (log-transformed regression y = 6.3911log(x)-80.671, R²=0.1497), indicating that species composition, size structure, and sampling discrepancies influence the acoustic response. Collectively, the findings of this study elucidate that single-beam hydroacoustics serve as an effective tool for delineating zooplankton spatial-vertical patterns, while the integration with traditional net sampling methodologies significantly enhances the monitoring of coastal ecosystems.